Taking a Closer Look at Photovoice as a Participatory Action Research Method. Issue 1 (2nd January 2017) - Sitter, Kathleen C.
ABSTRACT: This article involves an exploration into the ongoing claim that photovoice is a participatory action research (PAR) method. The article begins with a description of PAR and the theories that inform this methodology, followed by a brief history of photographic methods in research and the emergence of photovoice. The following section is an exploration of the goals and theories underlying photovoice, noting divergences from PAR in the following areas: 1) the positionality of the researcher, 2) decision-making power, and 3) the length of time dedicated to the overall process. The article concludes with further suggestions and considerations associated with photovoice and its implications to social work practice.